DAMPAK INDIKATOR PARIWISATA TERHADAP PERTUMBUHAN EKONOMI REGIONAL (STUDI PANEL PROVINSI-PROVINSI INDONESIA) - Parhimpunan Simatupang (JURNAL LENTERA BISNIS, 2024)
Tourism in Indonesia is still regarded as an ordinary industry. However, it has the potential to drive economic growth. This paper uses panel data regression to investigate how several tourism indicators, like tourist expenditure, accommodation availability, and number of workers, affect regional tourism revenue in Indonesia and how regional tourism revenue affects GRDP. Results show that domestic tourist expenditure and accommodation availability positively impact regional tourism revenue and are statistically significant. It was also found that the effect of regional tourism revenue on GRDP is positive and significant. It is recommended that the local government improve the quality and increase the quantity of accommodation. Keywords: Tourism Revenue, Tourism Labor, Tourist Expenditure, Accommodation, GRDP